Strategy to use the water rationally: Experience in a technical school, certified under ISO 14001: 2004 - Torres Salas, Theo Christian (2015)
On the coast of Peru, a region that concentrates 60% of the population and where a very high pressure on water resources exist, is beneficial to the National Service for Industrial Training (SENATI), have a strategy to use the water. To do this, set for its headquarters, located in the district of Independence, three axes to improve water use: Define control mechanisms, using appropriate technologies and maintain an environmental awareness among users. These axes allowed it to reduce wastes at the rate of 20% in the first year of implementation. From then until now, has been instrumental work in raising awareness among users about the importance of rational use of water, in order to continue to maintain average rates of 0,35 m3/person/year.